THE RELATIONSHIP BETWEEN SOCIAL CARE ACCESS AND HEALTHCARE USE BY OLDER ADULTS: A SYSTEMATIC REVIEW - Spiers, G.F. (Innov Aging, 2017)
Adult social care is facing substantial pressures in sustainability and accessibility, with consequences for the health sector. A systematic review was undertaken to synthesise evidence on the relationship between access to social care and healthcare utilisation outcomes for older adults. Social care access was defined using Gulliford et al.’s (2002) four domains: availability and supply, utilisation, quality and relevance, and equity. Systematic searches of published and grey literature were conducted, resulting in 11538 records. Titles and abstracts were screened for potential relevance, and full texts of selected studies assessed for inclusion against review criteria. Studies must have reported evidence about the relationship between social care access and healthcare utilisation specifically for older adults, and be published after 2000. A total of 45 studies were included in the review. Evidence was concentrated on the influence of two accessibility domains: social care availability and supply, and social care utilisation. No studies reporting evidence about the influence of social care quality or equity were identified. Evidence indicates that lower availability and supply of social care is associated with increased use of hospital care, particularly in UK studies. There is some indication than nursing home and residential care may have more influence than home based social care on healthcare utilisation. Evidence typically reflected secondary health care outcomes, with clear gaps regarding primary care use outcomes. This review offers a clear and timely picture of how access to social care influences healthcare use for older adults.